Georazčlenjevanje metapodatkovnega opisa kulturne dediščine - Vodeb, Vlasta (Knjižnica, 2012)
Geoparsing is a method for automatic extraction of geographic coordinates on the basis of unstructured text and content. The method is also usable for metadata of immovable, movable and intangible cultural heritage especially when geographic coordinates were not part of metadata description in documentation system. In this paper the usability and efficiency of online geoparsing services are presented, with the emphasis on e-service Europeana Geoparser. The analysis of spatial accuracy of the Europeana Geoparser is presented with the analysis of the Slovenian cultural heritage objects. At the end an evaluation of usability of the method for automated extraction of geographic coordinates for cultural heritage is given and debated.
Keywords: cultural heritage; kulturna dediščina; georazčlenjevanje; prostorske koordinate; digitalizacija; digitization; dokumentiranje; Europeana